2017
DOI: 10.1177/0885066617708558
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Electroacupuncture in Cardiac Anesthesia and Intensive Care

Abstract: The complementary use of EA for open-heart surgery reduces the duration of MV and ICU stay, blunts the inflammatory response, and might have protective effects on the heart. Our findings stimulate future RCT to provide definitive recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Evidence exists that an integrated health approach to perioperative care has the potential to improve a patient’s entire recovery process 25. In addition to opioids, CM therapies may help minimize the use of other perioperative pharmacologic agents (eg, benzodiazepines, propofol infusions, inhalational agents) 26–28. By reducing the doses of these agents, the associated side effects and the resources expended to treat these side effects may also be reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence exists that an integrated health approach to perioperative care has the potential to improve a patient’s entire recovery process 25. In addition to opioids, CM therapies may help minimize the use of other perioperative pharmacologic agents (eg, benzodiazepines, propofol infusions, inhalational agents) 26–28. By reducing the doses of these agents, the associated side effects and the resources expended to treat these side effects may also be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…By reducing the doses of these agents, the associated side effects and the resources expended to treat these side effects may also be reduced. For example, studies of perioperative acupuncture have reported a reduced incidence of postoperative nausea and delirium, decreased frequency of postoperative antiemetic use, and shorter times to extubation and discharge from the recovery room 11–17 27–29. Furthermore, studies suggest that CM therapies may also mitigate the body’s overall response to the stress of surgery 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis performed by Asmussen and colleagues reported that the complementary use of acupuncture could reduce the amounts of volatile anesthetics used during craniotomy and cardiac surgery, leading to faster extubation and postoperative recovery times. They also reported a lower incidence of postoperative nausea and vomiting (PONV) in patients receiving acupuncture [84,85]. Many of the POCD studies included in Table 1 also reported these beneficial effects of acupuncture.…”
Section: Reducing the Use Of Anesthetic Agents Promoting Patientmentioning
confidence: 97%
“…Acupuncture is a typical traditional Chinese medicine treatment for migraines, widely applied in clinical setting, [ 10 ] and it is recommended as a supplementary or alternative treatment for various diseases. [ 11 14 ] EA is a form of acupuncture, consisting of electrical impulses passing through needles to stimulate acupoints. [ 4 ] Although numerous studies have demonstrated the curative effect of EA on post-stroke incontinence, they were mired with questionable quality and inconsistencies in safety [ 15 ] and efficacy.…”
Section: Introductionmentioning
confidence: 99%